1989
DOI: 10.1177/000348948909801003
|View full text |Cite
|
Sign up to set email alerts
|

Air Conduction Thresholds and Secretory Otitis Media: A Conventional and Extra-High Frequency Audiometric Comparison

Abstract: A comparison has been made of air conduction threshold changes up to 1 year after myringotomy, aspiration of middle ear fluid, and insertion of ventilation tubes in ten patients with bilateral and 12 with unilateral secretory otitis media (SOM). Pure tone air conduction thresholds have been analyzed in three frequency groups: low frequency (LF; 0.25 0.5, and 1 kHz), high frequency (HF; 2, 4, and 8 kHz), and extra-high frequency (EHF; 10, 12, 14 and 16 kHz). In the LF and HF ranges, significant improvement came… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
9
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…It is interesting to note the frequency dependence time course of threshold improvement after middle ear intervention reported by Mair et al (1989). Their results using subjective audiometry are consistent with our ABR findings.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…It is interesting to note the frequency dependence time course of threshold improvement after middle ear intervention reported by Mair et al (1989). Their results using subjective audiometry are consistent with our ABR findings.…”
supporting
confidence: 90%
“…pressure changes at the round window) and also as suggested by Dr Mair (e.g. temporary retention of secretion and/or mucosal oedema; Mair et al (1989)).…”
mentioning
confidence: 87%
“…An explanation might be the history of bilateral otitis media with effusion, showing that previous otological disease results in higher thresholds and no difference between ears. 6 The absence of statistically significant differences between ears has also been reported in other papers, such as those by Frank & Dreisbach 45 , Hallmo, Borchgrevink & Mair, 43 and Mattews et al 44 This result is not common to all papers. Although Sayeb et al 34 found increased auditory sensitivity to the left at all the frequencies they studies, the difference was not statistically significant on the chosen method (ANOVA).…”
mentioning
confidence: 62%
“…Other papers corroborate these findings in cases presenting a history of otitis media with effusion. 6,7,36,39,37,48 There was a statistically significant difference in auditory thresholds between right and left ears in Group 2 children compared to those in Group 1 at all the frequencies we tested (9000, 10000, 11200, 12500, 14000, 16000, and 18000Hz) (Tables 7 and 8) (Charts 1 and 2). In the literature 5,6,49,39 various authors have found statistically significant differences in high frequency auditory thresholds between experimental groups and controls; in these studies the experimental groups consisted of children with at least four documented episodes of otitis media with effusion during.…”
mentioning
confidence: 78%
“…We observed a gradual lowering of hearing thresholds in the ventilation tube group. Mair et al 12 showed a gradually lowering of hearing thresholds after ventilation tube placement in patients with secretory otitis media. Browning et al 13 emphasized that natural resolution of OME over led to improved hearing in subjects.…”
mentioning
confidence: 99%